2017
DOI: 10.1093/nar/gkx1258
|View full text |Cite
|
Sign up to set email alerts
|

ZNF830 mediates cancer chemoresistance through promoting homologous-recombination repair

Abstract: Homologous recombination (HR), which mediates the repair of DNA double-strand breaks (DSB), is crucial for maintaining genomic integrity and enhancing survival in response to chemotherapy and radiotherapy in human cancers. However, the mechanisms of HR repair in treatment resistance for the improvement of cancer therapy remains unclear. Here, we report that the zinc finger protein 830 (ZNF830) promotes HR repair and the survival of cancer cells in response to DNA damage. Mechanistically, ZNF830 directly partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…These results suggest that ZNF281 levels could be used to predict patients' responsiveness to DNA-damaging treatments. In line with this finding, another zinc finger protein, ZNF830, has been recently implied in the chemoresistance to genotoxic therapies, as a consequence of its role in promoting DNA repair by HR [36]. Furthermore, the strong correlation between ZNF281 recruitment and PARP activity (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…These results suggest that ZNF281 levels could be used to predict patients' responsiveness to DNA-damaging treatments. In line with this finding, another zinc finger protein, ZNF830, has been recently implied in the chemoresistance to genotoxic therapies, as a consequence of its role in promoting DNA repair by HR [36]. Furthermore, the strong correlation between ZNF281 recruitment and PARP activity (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, pharmacological inhibition of CDK1/2 sensitizes glioblastoma cells to temozolomide [53]. A recent study demonstrated that zinc finger protein 830 (ZNF830) plays a role in the repair of DNA double-strand breaks and that knockdown of ZNF830 sensitizes lung cancer cells to olaparib, a DNA-damaging agent [54]. In addition, the importance of miRNAs in the regulation of DNA repair mechanisms has been underscored.…”
Section: Dna Damage Repair In Cancermentioning
confidence: 99%
“…Now the data are included in BioStudies database, which is a public health database. Our study did not require the approval of an ethics committee as it is a secondary analysis of BioStudies database of a public database and of free access (Alarconruiz, Heredia & Tayperondan, 2019;Sarkans et al, 2018). This article does not contain any studies with human participants or animals performed by any of our authors.…”
Section: Additional Information and Declarations Fundingmentioning
confidence: 99%